Juridical Analysis of the Imposition of VAT on Contra Discount Revenue in Supreme Court Decision Number 5926B/PK/PJK/2025 - Gunardi Lie; Aufa Fakhrana Rizky (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines various legal issues arising in the application of Value Added Tax (VAT) on the utilization of Taxable Services obtained from outside the customs territory. Focusing on the classification of Contra Discount Revenue in the credit card industry. This study is motivated by differing interpretations between tax authorities and taxpayers regarding the scope of financial services that are excluded from taxable objects. This research applies a normative juridical method with a case-based approach, conducted through an analysis of Supreme Court Decision Number 5926/B/PK/PJK/2025, this study examines the judges' considerations in canceling fiscal corrections. The results show that Contra Discount Revenue is substantially an integral part of credit card business operations as regulated in Article 4A paragraph (3) letter d of the VAT Law, therefore it is not appropriate to classify it asmanagement service fees subject to VAT. This Supreme Court Decree reaffirms the supremacy of the substance over form principle, which requires tax authorities to ensure legal certainty and fairness for taxpayers in the cross-border financial sector.